Design and optimization of single, double and multilayer anti-reflection coatings on planar and textured surface of silicon solar cells. (August 2022) - Valiei, Maryam; Shaibani, Parman Mojir; Abdizadeh, Hossein; Kolahdouz, Mohammadreza; Asl Soleimani, Ebrahim; Poursafar, Jafar
Abstract: The present silicon solar cell industry's main concern is to increase efficiency by minimizing the surface reflection. As a result, lately, much attention has been paid to the composition and number of the layers used for anti-reflection coatings in order to reduce surface reflection. In the present work, single, double, triple, and quadruple anti-reflection coatings on silicon solar cells have been designed and optimized using FDTD and PC1D simulation methods. The different combinations of SiO2, SiON, Si3 N4, and SiNx coatings on both planar and textured surfaces were simulated and their optical and electrical parameters were investigated. Compared to planar surfaces, the designed coatings on textured surfaces showed better optical and electrical results for almost all investigated parameters. On textured surfaces, SiO2 /Si3 N4 /SiNx acquired the lowest weighted average reflection (0.121%), SiO2 /SiNx, SiON/SiNx, SiO2 /Si3 N4 /SiNx, and SiO2 /SiON/Si3 N4 /SiNx the highest Jsc (38.5 mA/cm 2 ) and finally SiO2 /Si3 N4 /SiNx and SiO2 /SiON/Si3 N4 /SiNx both the highest Voc (705.7 mV) and η(23%). Graphical Abstract: ga1 Highlights: Single, double, triple, and quadruple anti-reflection coatings on silicon solar cells have been designed and optimized using simulation methods. The optical and electrical parameters of different combinations of SiO2, SiON, Si3N4, and SiNx coatings were. investigated. Compared to planar surfaces, the designed coatings on textured surfaces showed better optical and electrical results . On textured surfaces, SiO2/Si3N4/SiNx acquired the lowest weighted average reflection (0.121%).